Two optical coherence tomography systems detect topical gold nanoshells in hair follicles, sweat ducts and measure epidermis. Issue 9 (19th June 2018) - Mogensen, Mette; Bojesen, Sophie; Israelsen, Niels M.; Maria, Michael; Jensen, Mikkel; Podoleanu, Adrian; Bang, Ole; Haedersdal, Merete
Abstract : This study provides novel data on gold nanoshells (GNSs) used as contrast agent in 2 optical coherence tomography (OCT) systems. GNS topically applied and massaged into skin generating increased signals from natural skin openings. This study suggests that GNS is an interesting candidate for increasing sensitivity in OCT diagnosis of hair and sweat gland disorders and has potential for topical drug delivery and that choice of OCT systems matters. Abstract : Optical coherence tomography (OCT) is an established imaging technology for in vivo skin investigation. Topical application of gold nanoshells (GNS) provides contrast enhancement in OCT by generating a strong hyperreflective signal from hair follicles and sweat glands, which are the natural skin openings. This study explores the utility of 150 nm diameter GNS as contrast agent for OCT imaging. GNS was massaged into skin and examined in four skin areas of 11 healthy volunteers. A commercial OCT system and a prototype with 3 μm resolution (UHR‐OCT) were employed to detect potential benefits of increased resolution and variability in intensity generated by the GNS. In both OCT‐systems GNS enhanced contrast from hair follicles and sweat ducts. Highest average penetration depth of GNS was in armpit 0.64 mm ± SD 0.17, maximum penetration depth was 1.20 mm in hair follicles and 15 to 40 μm in sweat ducts. Pixel intensity generated from GNS in hair follicles was significantly higher in UHR‐OCT images ( P = .002) and epidermal thickness significantly lower 0.14 vs 0.16 mm ( P = .027). This study suggests that GNSs are interesting candidates for increasing sensitivity in OCT diagnosis of hair and sweat gland disorders and demonstrates that choice of OCT systems influences results.